THE ROLE OF SOCIAL AND ENVIRONMENTAL FACTORS IN FORMING A GROUP OF SICKLY CHILDREN FROM SOCIALLY-SECURED FAMILIES OF MOSCOW - N. A. Abramova; M. S. Savenkova (LLC "Diagnostics and Vaccines", 2015)
Many factors contributing to the formation of a group of sickly children were analyzed according to the modern statistical mathematical methods. In this paper we consider the role of the living and environmental factors. It should be emphasized that all 143 (120 children made up observation group and 23 the control group) observed the child live in good conditions in socially-secured families.